Studies on Matter Production of Taro Plant (Colocasia esculenta Schott) : II. Varietal differences of dry matter production and tuber growth - SATOU, Tooru; MIYAUCHI, Eiji; SUGIMOTO, Hideki (Japanese Journal of Crop Science, 1988)
The dry matter production of three types of taro plant was examined and growth behaviours were analyzed. The types were classified into three groups based on the characteristics of tuber growth. The first group was named 'daughter tuber' because of the conspicuous growth of the daughter tuber, the second 'mother and daughter tuber' and the third 'mother tuber'. In the experiment, 'Ishikawawase', 'Onnawase' of the first group, 'Akame' of the second and 'Taiwan-imo' of the third group were used. 1. Behavious of the individual tuber growth differed so much among the groups. The growth increment of the daughter tuber and the secondary corm of 'Ishikawawase' as well as of 'Onnawase' was great while that of 'Akame' was conspicuous mainly in the daughter and mother tuber. The mother tuber of 'Taiwan-imo' continued to grow until the end of the season. 2. In the latter half of the season, the crop growth rate of 'Akame' and 'Taiwan-imo' was increased. An analysis of the crop growth rate and the tuber growth rate showed that the tuber increment contributed to the increase of the CGR. 3. It was postulated that an increase in the leaf area index of 'Akame' and 'Taiwan-imo' resulted in an increase in the tuber growth rate.